2002
DOI: 10.1046/j.1365-2702.2002.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

`Seeking': a key activity for new family carers of stroke survivors

Abstract: Stroke is one of the major causes of disability in the United Kingdom and considerable numbers of stroke survivors need help and support from family carers. The sudden and unexpected nature of stroke means that there is very little time for family members to prepare for a caring role. This paper draws on data from 37 interviews with 14 new carers of stroke survivors and highlights the uncertainty and lack of confidence that family members experience in adopting a caring role. During the initial period followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 34 publications
(49 reference statements)
6
109
1
1
Order By: Relevance
“…90 -92 Caregiving can result in lifestyle changes 89,93 as well as physical, emotional, and financial problems. 90,94 -96 It was also reported that carers feel isolated, that their own needs are neglected, 91 and that family relationships can suffer. 96 Carers develop their own strategies including trying to increase their competence, 91 creating their own solutions for patient's functional loss, constructing their own sense of what recovery means, 97 and using their own spiritual beliefs and practices.…”
Section: Mckevitt Et Al Qualitative Studies Of Stroke: a Systematic Rmentioning
confidence: 99%
“…90 -92 Caregiving can result in lifestyle changes 89,93 as well as physical, emotional, and financial problems. 90,94 -96 It was also reported that carers feel isolated, that their own needs are neglected, 91 and that family relationships can suffer. 96 Carers develop their own strategies including trying to increase their competence, 91 creating their own solutions for patient's functional loss, constructing their own sense of what recovery means, 97 and using their own spiritual beliefs and practices.…”
Section: Mckevitt Et Al Qualitative Studies Of Stroke: a Systematic Rmentioning
confidence: 99%
“…It is easier to endure waiting once one knows what one is waiting for and why [5,20] . The importance of informing the family has also been found in earlier studies [6,23] .…”
Section: Analysis Of the Research Results And Improving The Informatimentioning
confidence: 57%
“…[12] However, the support and assistance provided by health and social services for the families are often insufficient or not suited to experienced needs. [22,23] A family systems nursing intervention, such as FamHC, has the potential to be a way of supporting families' needs, but this still has to be evaluated from various perspectives. It has previously been shown that family systems nursing interventions can lead to family responses such as improved understanding and capability, enhanced coping, caring more about each other and the family, improved family and individual emotional well-being, improvement in interactions within and outside family, and healthier individual behaviour.…”
Section: Family Supportmentioning
confidence: 99%